1999
DOI: 10.1063/1.123444
|View full text |Cite
|
Sign up to set email alerts
|

On the nature of the electric-field effect on YBa2Cu3O7−δ grain boundary junctions employing epitaxial SrTiO3 gate insulators

Abstract: We have fabricated Josephson field-effect transistors based on YBa2Cu3O7−δ bicrystal grain-boundary junctions (GBJs) and epitaxial SrTiO3 films as gate insulators. The SrTiO3 gate insulator shows high products of the breakdown field Ebd and the dielectric constant εr up to Ebdεr=1.3×1010 V/m allowing measurements over a wide range of applied gate electric-field Eg. The critical current Ic of the GBJs is found to depend highly nonlinear on Eg. Remarkably, the measured Ic(Eg) are very similar to the εr(Eg) curve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…Using a Ginzburg-Landau-based model it was shown that the I c changes observed by Dong and collaborators are consistent with a field-induced change in the carrier density in the Josephson junction (Betouras et al, 1996). As the measured I c changes were found to scale with the field-dependent, nonlinear dielectric constant of the gate insulator ⑀ r , it was proposed that the effects were caused by an assumed giant piezoelectric effect of the epitaxial SrTiO 3 gate layer (Petersen, Takeuchi, et al, 1995;Windt et al, 1999; see also Grupp and Goldman, 1997). As this hypothesis accounts for neither the small values of the field-induced changes of R n nor the proportionality of the I c changes with ⑀ r , it seems more likely that the electric fringe fields arising from charges embedded in the grain boundaries are affected by the gate field-induced change of ⑀ r .…”
Section: A Applied Electric Fieldsmentioning
confidence: 77%
“…Using a Ginzburg-Landau-based model it was shown that the I c changes observed by Dong and collaborators are consistent with a field-induced change in the carrier density in the Josephson junction (Betouras et al, 1996). As the measured I c changes were found to scale with the field-dependent, nonlinear dielectric constant of the gate insulator ⑀ r , it was proposed that the effects were caused by an assumed giant piezoelectric effect of the epitaxial SrTiO 3 gate layer (Petersen, Takeuchi, et al, 1995;Windt et al, 1999; see also Grupp and Goldman, 1997). As this hypothesis accounts for neither the small values of the field-induced changes of R n nor the proportionality of the I c changes with ⑀ r , it seems more likely that the electric fringe fields arising from charges embedded in the grain boundaries are affected by the gate field-induced change of ⑀ r .…”
Section: A Applied Electric Fieldsmentioning
confidence: 77%
“…In figure 3 we present the result for the surface critical field (18) versus the external bias (4). We see that the external bias can enhance or decrease the surface critical value depending on the field direction.…”
Section: Surface Critical Fieldmentioning
confidence: 97%
“…The results revealed that the degraded SrTiO 3 layer is very thin and the dielectric constant of the SrTiO 3 film was dominated by that of single-crystal-like SrTiO 3 layer. For most high temperature superconducting devices such as the field effect transistor (FET), [1][2][3][4][5] a highly epitaxial insulation layer sandwiched between superconducting films is necessary. To obtain a large magnitude of the electric field effect in FET's, both a high breakdown electric field E d and a high dielectric constant " r are required for the gate insulator.…”
Section: Structure and Dielectric Behavior Of Epitaxially Grown Srtiomentioning
confidence: 99%
“…However, even this value is only a half of that of the STO single crystal. The development of STO films with larger dielectric constants is substantial for the future application, 3,[15][16][17] since the seriously depressed " r limits the area of applications of STO thin films.…”
Section: Structure and Dielectric Behavior Of Epitaxially Grown Srtiomentioning
confidence: 99%